Rose Hip Seed Oil: Methods of Extraction and Chemical Composition - Dąbrowska, Mariola; Maciejczyk, Ewa; Kalemba, Danuta (European journal of lipid science and technology, 2019)
Recently, there has been growing interest in the use of uncommon plant oils in the food and cosmetic industries. Oils obtained from Rosa canina L. and R. rubiginosa L. seeds are widespread on the market and recommended for pharmaceutical, cosmetic, and nutritional purposes. Both these oils are quite well investigated. However, Rosa L. genus includes numerous other species bearing fruits (hips) with seeds rich in active compounds. These rose species may also be a source of oil valuable for purposes above mentioned. Thus recent literature relating to rosehip seed oils, its extraction methods and composition are summarized to provide an overview of the published data on this subject. The goal of this article is to deliver necessary background with references for an up‐to‐date perspective of different rose species' seed oils, to review methods for their isolation, and thereby to compare oil extraction yield and composition. Practical Applications: This review underscores the importance of rose hip seed oil as a product for healthier foods and other purposes. Uncommon plant oils have recently gained popularity in the food and cosmetic industries. Oils obtained from Rosa canina and R. rubiginosa seeds are recommended for pharmaceutical, cosmetic, and nutritional purposes. Moreover, Rosa L. genus includes numerous other species' seeds rich in active compounds. Thus recent literature relating to rose hip seed oils, its extraction methods, and composition are summarized to provide an overview of the published data on this subject. Uncommon plant oils have recently gained popularity in the food and cosmetic industries. Oils obtained from Rosa canina and R. rubiginosa seeds are recommended for pharmaceutical, cosmetic, and nutritional purposes. Moreover, Rosa L. genus includes numerous other species' seeds rich in active compounds. Thus recent literature relating to rose hip seed oils, its extraction methods, and composition are summarized to provide an overview of the published data on this subject.